Efecto del pH sobre la supervivencia embrionaria, periodo embrionario y de eclosión de Galaxias maculatus - Barile,Juan (Universidad de Valparaíso. Facultad de Ciencias del Mar, 2016)
This study aims to evaluate the effect of pH on embryonic survival of Galaxias maculatus. Embryos were incubated at 6 different pH levels in the water. One-way ANOVA was used to compare averages between treatments and Tukey test to determine post hoc differences. The Probit regression was used to estimate the embryonic and the hatching period. Embryos survive pH from 5 to 11 and die at pH extremes 3 and 13. The best average survival rates were obtained at neutral pH (78.7 ± 1.2) and as the pH decreases away from embryonic survival 7 embryonic survival decreases. In conclusion, pH is an important factor to consider for the production of larval G. maculatus.